2022
DOI: 10.4103/2773-2398.339171
|View full text |Cite
|
Sign up to set email alerts
|

The role of neuromodulation to drive neural plasticity in stroke recovery

Abstract: Stroke is one of the leading causes of death and adult disability globally, representing one of the highest burdens of disease worldwide. Recent advancements of neuromodulation techniques emerge as promising tools for enhancing stroke recovery, such as transcranial electric stimulation and transcranial magnetic stimulation, which can induce short- and long-term changes of synaptic excitability to restore the impaired functions in stroke patients. The review focuses on discussing the neuroplastic mechanisms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Stroke is one of the leading causes of death and adult disability globally ( Wang, 2022 ). A total of 75% of patients who sustain a stroke have limitations in walking ( Abilleira et al, 2005 ), and the most common pattern of walking impairment post-stroke is hemiparetic gait.…”
Section: Introductionmentioning
confidence: 99%
“…Stroke is one of the leading causes of death and adult disability globally ( Wang, 2022 ). A total of 75% of patients who sustain a stroke have limitations in walking ( Abilleira et al, 2005 ), and the most common pattern of walking impairment post-stroke is hemiparetic gait.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, the upregulation of Fyn through neuromodulation may also benefit several aspects such as neuronal migration, synaptogenesis, and synaptic plasticity [ 100 , 101 ]. Neuromodulation is essential for synaptogenesis and plasticity [ 102 ]. Increasing Fyn activity promotes actin dynamics allowing oligodendrocyte maturation and facilitating synaptic regeneration, and subsequent myelin production [ 103 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have reported that neuromodulation techniques have been extensively studied and proved to be effetely in many diseases' treatment (Pan et al, 2022 ; Wang, 2022 ), such as repetitive functional magnetic stimulation (rFMS) alleviated the urinary retention for the patients after spinal cord injury (Zhang et al, 2022 ), promote the rehabilitation after brain tumor surgery (Dadario et al, 2022 ); Electrical nerve stimulation, which has been used for treating neuropathic pain, has been shown to be an effective treatment for reducing spasticity (Fernández-Tenorio et al, 2019 ; Tapia Pérez, 2019 ). The reduction in spasticity by functional electrical stimulation (FES) has also been confirmed by clinical studies, including a significant reduction in quadriceps tone in incomplete spinal cord patients and an increase in voluntary muscle strength after receiving FES (Granat et al, 1993 ).…”
Section: Discussionmentioning
confidence: 99%